2020
DOI: 10.1111/mec.15662
|View full text |Cite
|
Sign up to set email alerts
|

Quorum‐sensing signaling by chironomid egg masses’ microbiota, affects haemagglutinin/protease (HAP) production by Vibrio cholerae

Abstract: Vibrio cholerae, the causative agent of cholera, is commonly isolated, along with other bacterial species, from chironomid insects (Diptera: Chironomidae). Nevertheless, its prevalence in the chironomid egg masses’ microbiota is less than 0.5%. V. cholerae secretes haemagglutinin/protease (HAP) that degrades the gelatinous matrix of chironomid egg masses and prevents hatching. Quorum sensing (QS) activates HAP production in response to accumulation of bacterial autoinducers (AIs). Our aim was to define the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

6
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
(100 reference statements)
0
19
0
Order By: Relevance
“…Vibrio cholerae degrades the egg masses' glycoprotein matrix by secreting haemagglutinin protease, while Aeromonas degrades chitin by secreting chitinases. This egg mass degradation prevents larval hatching and thus, controls chironomid population levels on the one hand (Halpern, 2010) and may support the maintenance of the egg mass's endogenous bacterial communities, on the other hand, by supplying them with available nutrients Sela et al, 2020). Thus, the presence of V. cholerae and Aeromonas species in all four life stages of C. transvaalensis might represent a mutualistic relationship between these species and their natural host.…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio cholerae degrades the egg masses' glycoprotein matrix by secreting haemagglutinin protease, while Aeromonas degrades chitin by secreting chitinases. This egg mass degradation prevents larval hatching and thus, controls chironomid population levels on the one hand (Halpern, 2010) and may support the maintenance of the egg mass's endogenous bacterial communities, on the other hand, by supplying them with available nutrients Sela et al, 2020). Thus, the presence of V. cholerae and Aeromonas species in all four life stages of C. transvaalensis might represent a mutualistic relationship between these species and their natural host.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, almost half of the microbial community that was identified in C. transvaalensis egg masses belonged to bacterial genera that might have the ability to protect the insect under stress conditions [ 11 ]. The first instar larva feeds on the egg mass remains which contain both nutrients and endogenous microorganisms [ 12 ]. It is hypothesized that the microbiota that inhabits the egg mass protects the insect along its metamorphosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“… Vibrio cholerae is a wide-spread gastrointestinal pathogen that has caused seven cholera pandemics ( 22 ). The bacterium is found in polymicrobial marine ecosystems in association with copepods, fish, and insects ( 23 25 ). V. cholerae employs T6SS effectors that disrupt cell envelopes and contribute to pathogenicity in hosts ( 26 33 ).…”
Section: Introductionmentioning
confidence: 99%